Bentuk Komunikasi Netlingo Dalam Pola Komunikasi Remaja - Wulandari, Ananda; Hasmawati, Fifi; Muslimin, Muslimin (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
Netingo is a form of communication adapted from social media, where words or messages are conveyed in sounds that are not in accordance with good rules. However, Netlingo is used when communicating with those who already have an understanding. Typing errors, capitalization errors and punctuation errors are commonplace in Netlingo. This is because of the assumption that the text is speaking so that grammar is not important. The pattern of communication referred to by the author is the form or way teenagers currently communicate. Adolescence is a period from which the human age experiences the most changes, thus bringing it from childhood to adulthood. The changes that occur include aspects of human life that are physical, spiritual, thoughts, feelings and social. The use of Netlingo is felt to have become a verbal oportoir for the majority of young people today. The problem is that there is still a competency disparity between the young and the old, causing misperceptions which in time will lead to miscommunication between them. In practice, the linguistic creativity of young people (adolescents) has given rise to language divergence, so it is not surprising that the Netlingo phenomenon has created disparities or differences in communication between young people and old people in society.